The Choice of Anticoagulant Influences the Characteristics of Bone Marrow Aspirate Concentrate and Mesenchymal Stem Cell Bioactivity In Vitro - Ryan C. Dregalla; Jessica Ann Herrera; Lucanus Steven Koldewyn; Edward Jeffery Donner (Hindawi Limited, 2022)
Bone marrow aspirate concentrate (BMC) is commonly used as a therapeutic agent to resolve orthopedic injuries, using its unique cellularity to reduce inflammation and prime the region for repair. The aspiration of the bone marrow is performed using either sodium citrate (SC) or heparin sodium (HS) as an anticoagulant and processed via centrifugation to concentrate the cellular constituents. To date, the consideration of the impact of the two commonly used anticoagulants on the mesenchymal stem/stromal cell (MSC) population has been overlooked. The current study assesses the differences in the BMCs produced using 15% SC and HS at 1,000 U/mL or 100 U/mL final v./v. as an anticoagulant using in vitro metrics including total nucleated cell counts (TNC) and viability, the ability for mesenchymal stromal/stem cells (MSCs) to establish colony-forming units with fibroblast morphology (CFU-f), and cytokine expression profile of the MSC cultures. Our findings demonstrate that HS-derived BMC cultures result in higher CFU-f formation and CFU-f frequency at both concentrations assessed compared to SC-derived BMC cultures. In addition, there were significant differences in 27% (7 of 26) of the cytokines quantified in HS-derived BMC cultures compared to SC-derived BMC cultures with implications for MSC plasticity and self-renewal.